PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PT KERETA API INDONESIA (PERSERO) DIVISI REGIONAL II SUMATRA BARAT PADANG PARIAMAN - Yulia Ningsih; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Sumatra Barat Kereta Api Indonesia,This research aims to determine the effect of service quality loward sanisfaction. Service quality as independen as independen variable (x) and sanissfaction as independen variable (y)The research sample are 100 responen of the population by using the slovin formula. Data was obtained from the questionnaire and subsequently processed to then be tested with the help of statistics through SPSS. The result of calculation of the determination coefficient is 0,533. It means, service quality affects sanisfaction is 55,3% in. PT Kereta Api Indonesia (Persero) Divisi Regional II Sumatra Barat Padang PariamanKeywords: Service quality, Sanisfaction